Evaluation Du Système D’hygiène Dans Les Locaux Des Restaurationsscolaires, À La Région d’El Gharb Cherardabnihssen, Par Rapport Auxexigences Normatives Internationales - El Ghaza, S.; Chbab, Y.; Bakrim, E.; Zaadoud, B.; Chaouch, A. (European Scientific Journal, ESJ, 2017)
The implementation of hygiene system in the school catering is based on the application of good hygienic practice and regulations of food safety (security). These measures of hygiene contribute absolutely, in the elimination of the potential food risks susceptible to be at the origin of several diseases. This article presents the results of a study carried out to evaluate the degree of the respect for the sanitary conditions at the level of three school restaurants. The result of our study aims to determine the level of compliance of their hygienic systems to international hygienic standards. The rates of conformity of the sites of the study were of the order of 33, 60 %, 33, 00 % and of 48, 58 % respectively at the level of the establishment n°1, n°2 and n°3. The recorded results show apparently, the level of conformity with regard to the standards. In front of this situation, it is essential to plan and to implement relevant actions of improvement and to engage ways and resources to eliminate the noticed gaps and increase the level of conformity